A study on the correlation of thyroid nodules with METS-IR and SII in a population undergoing health checkups - Guan, Ruoping; Dai, Guokui; Ye, Chuanjiang; Cai, Xiangsheng (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the associations between thyroid nodules and two emerging biomarkers-Metabolic Score for Insulin Resistance (METS-IR) and Systemic Immune-Inflammation Index (SII)-in adults undergoing routine health checkups.MethodsIn this retrospective cross-sectional study, we analyzed data from 49,835 adults (65.50% male, 34.50% female) who underwent health checkups in 2023. Thyroid nodules were classified using the Thyroid Imaging Reporting and Data System (TI-RADS) categories (2, 3, ≥4). Statistical analyses, including chi-square tests and multiple logistic regression, were used to evaluate the relationships between nodule prevalence, sex, age, thyroid-stimulating hormone (TSH) levels, METS-IR, and SII.ResultsThyroid nodules were detected in 60.12% of the participants. The prevalence of TI-RADS 2, 3, and ≥4 nodules were 20.61%, 37.81%, and 1.69%, respectively. Nodule prevalence was significantly higher in women (70.07%) than in men (54.87%, P < 0.001). After multivariable adjustment, TI-RADS categories 2, 3, and ≥4 nodules were independently associated with female sex and increasing age (all P < 0.001). Notably, TI-RADS 2 and 3 nodules exhibited an inverse association with serum TSH levels (P < 0.001 for both), whereas TI-RADS 3 and ≥4 nodules showed positive associations with elevated METS-IR and SII values (P < 0.05 for all comparisons).ConclusionThyroid nodules are highly prevalent, particularly among women and older individuals. Lower-grade nodules (TI-RADS 2 and 3) show an inverse correlation with TSH levels, whereas higher-grade nodules (TI-RADS 3 and ≥4) are independently linked to increased insulin resistance (METS-IR) and systemic inflammation (SII). These findings suggest that METS-IR and SII could serve as valuable biomarkers for thyroid nodule assessment.